2002
DOI: 10.1177/002215540205000606
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide System Gene Expression in Human Coronary Arteries

Abstract: S U M M A R YThe natriuretic peptides (NPs) ANF, BNP, and CNP have potent anti-proliferative and anti-migratory effects on vascular smooth muscle cells (SMCs). These properties make NPs relevant to the study of human coronary atherosclerosis because vascular cell proliferation and migration are central to the pathophysiology of atherosclerosis. However, the existence and cytological distribution of NPs and their receptors in human coronary arteries remain undetermined. This has hampered the development of hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 32 publications
8
68
0
2
Order By: Relevance
“…Furthermore, GCB is expressed at the site of vascular injury. These results and that of others [50] support the concept that CNP and GCB undergo changes in expression in relation to the progression of an atherosclerotic lesion in humans. The prominence of CNP is particularly evident in endothelial cells and in plaque microvessels and adventitial vasa vasorum, and therefore it is reasonable to speculate a role for CNP-GCB signaling in vascular remodeling and in the progression or regression of plaques.…”
Section: Clinical Implications Of C-type Natriuretic Peptidesupporting
confidence: 88%
“…Furthermore, GCB is expressed at the site of vascular injury. These results and that of others [50] support the concept that CNP and GCB undergo changes in expression in relation to the progression of an atherosclerotic lesion in humans. The prominence of CNP is particularly evident in endothelial cells and in plaque microvessels and adventitial vasa vasorum, and therefore it is reasonable to speculate a role for CNP-GCB signaling in vascular remodeling and in the progression or regression of plaques.…”
Section: Clinical Implications Of C-type Natriuretic Peptidesupporting
confidence: 88%
“…Recent studies have also demonstrated that myocardial perfusion abnormalities on 201Tl myocardial scintigraphy and late gadolinium enhancement on cardiac magnetic resonance imaging are frequently observed in patients with asymptomatic TA 32,33) . Consequently, subclinical myocardial ischemia may induce the production of NT-proBNP from the intima in human coronary arteries 34) . Hence, the alterations related to increased arterial stiffness may stimulate the synthesis and release of NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have helped establish the major functions of CNP as being either paracrine or autocrine in nature, rather than endocrine. In keeping with its limited range of action, CNP expression is normally confined to those tissues and organs in which it exerts a regulatory role, principally the brain and pituitary [82], cardiovascular system [11,23,38,69,98], endochondral bone [102], and the male [100] and female [95,103] reproductive systems. CNP transcript and/or protein have also been identified in a number of tissues and organs where its functional role has yet to be defined [9,76,77,94].…”
Section: C-type Natriuretic Peptidementioning
confidence: 99%
“…A study of CNP expression in human neointimal SMC following angioplasty [56] pointed to a similar, time-dependent up-regulation of CNP in the human SMC that was maintained for at least six months after surgical intervention. Casco et al [11], using immunohistochemistry, identified CNP in both medial and intimal SMC of early through advanced atherosclerotic lesions, but the relationship of CNP to lesion stage was not described. CNP expression has also been studied in human aortic valves with increasing severity of stenosis, a condition that has many of the hallmarks of atherosclerosis, including early inflammation and later fibrosis and calcification [68].…”
Section: Cnp Regulation In Cardiovascular Diseasementioning
confidence: 99%